Multi-Omics Approach in the Identification of Potential Therapeutic Biomolecule for COVID-19 - Singh, Rachana; Singh, Pradhyumna Kumar; Kumar, Rajnish; Kabir, Md. Tanvir; Kamal, Mohammad Amjad; Rauf, Abdur; Albadrani, Ghadeer M.; Sayed, Amany A.; Mousa, Shaker A.; Abdel-Daim, Mohamed M.; Uddin, Md. Sahab (Frontiers in Pharmacology, 2021)
COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It has a disastrous effect on mankind due to the contagious and rapid nature of the spread. Though the vaccines for SARS-CoV-2 are successfully developed, the proven, effective, and specific therapeutic molecules are yet to be identified for the treatment. The repurposing of existing drugs and recognition of new medicines are continuously in process. Efforts are being made to single out plant-based novel therapeutic compounds. As a result, some of these biomolecules are in their testing phase. During these efforts, the whole-genome sequencing of the SARS-CoV-2 has given the direction to explore the omics systems and approaches to overcome this unprecedented health challenge globally. Genome, proteome, and metagenome sequence analysis have helped identify virus nature, thereby assisting in understanding the molecular mechanism, structural understanding, and disease propagation. The multi-omics approaches offer various tools and strategies for identifying potential therapeutic biomolecules for COVID-19 and exploring the plants producing biomolecules that can be used as biopharmaceutical products. This review explores the available multi-omics approaches and their scope to investigate the therapeutic promises of plant-based biomolecules in treating SARS-CoV-2 infection.